Development of the Environmental Friendly Non-Aqueous Tape Casting Process for High-Quality Si3N4 Ceramic Substrates. (November 2019) - Hou, Qingdong; Luo, Xudong; Xie, Zhipeng; An, Di; Xiao, Zhicai; Ma, Bin
Abstract: A cheap and environmental friendly non-aqueous tape casting process for preparing high quality Si3 N4 ceramic substrates was explored. A ternary solvent mixture of ethanol, ethyl acetate and butyl acetate-based formula was developed by using castor oil, polyvinyl butyral and dibutyl phthalate as the dispersant, binder and plasticizer, respectively. The influence of dispersant content, binder content and solid loading on the rheological properties of Si3 N4 slurries was firstly investigated. It was found that the optimized formulation for dispersant, binder and solid loading was 1.6 wt%, 12 wt% and 51 wt%, respectively. The flat, flexible and uniform green tapes with a thickness of 400–500 μm and high-quality including high bulk density, uniform pore distribution and low porosity were obtained. After drying and debinding, the green sheets were sintered at 1900 °C for 2 h, where Si3 N4 ceramics with a thermal conductivity being 85.79 W·m −1 ·K −1 can be achieved. The sintered samples were one of the most attractive substrate materials for high power electronics applications.